PEMAHAMAN AKAN ROH NUBUAT DI KALANGAN SISWA SMA PERGURUAN ADVENT BANDUNG - Reymand M. Hutabarat; Francis M. Hutabarat (Jurnal Koinonia, 2013)
The Seventh-day Adventist (SDA) church considersherself as the Remnant Church based on Revelation 12:17, which says that the church keep “the commandments of God” and have “the testimony of Jesus.” According to Revelation 19:10, “the testimony of Jesus is the Spirit of Prophecy.Â  Therefore, the Spirit of Prophecy is an integral part of the SDA Church. Bandung Adventist Academy is a school that is located in the heart of Bandung city, and has a good number of SDA students.Â  This article tries to find the perception on understanding of the spirit of prophecy in that school, where at the end it is found that generally the students have good understandings regarding the spirit of prophecy.